Spatial Literacy in Geometry Learning: A Systematic Literature Review - Octaria, Dina; Zulkardi, Zulkardi; Putri, Ratu Ilma Indra; Hiltrimartin, Cecil (Universitas PGRI Palembang, 2024)
Spatial literacy, as a subset of mathematical literacy, integrates three core domains: visualization, reasoning, and communication. This systematic literature review aims to investigate the application of spatial literacy in geometry education, drawing on existing research findings, and to identify strategies that effectively enhance students' spatial skills within this context. Employing the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines ensures a systematic and structured approach to the review process. Data were sourced from platforms such as Google Scholar, Web of Science, and Scopus, encompassing publications from 2020 to 2024. The findings reveal that spatial literacy in geometry education is fostered through the use of visual aids, geometric models, activities emphasizing mental rotation and transformation, and the integration of spatial language. Additionally, strategies to improve students' spatial literacy include leveraging technology, implementing project-based learning, fostering collaborative group work, and engaging students in physical exploration.